Hemodynamic Instability during Intermittent Hemodialysis in ICU Patients with Abnormal Capillary Refill Time: Hemodynamic Instability in Intensive Care Unit Patients - Jamil, Araj; Hashmi , Madiha; Rasheed, Ghulam; Muzaffar, Saima; Ahmad, Bashir; Ahmed, Shakeel (Pakistan Journal of Health Sciences, 2024)
Intradialytic Hemodynamic Instability (IHI) may cause delay in renal recovery and also increases risk of mortality. Capillary Refill Time (CRT) was a stress free method used for peripheral perfusion that becomes worse during circulatory failure. Objective: To determine Hemodynamic Instability during Intermittent Hemodialysis in ICU Patients with Abnormal Capillary Refill Time at a tertiary care hospital, Karachi, Pakistan. Methods: This was the 06 months’ data collection, 1-year prospective observational study. Overall 137 patients were evaluated via sampling technique of non-probability consecutive sampling technique. For each intermittent hemodialysis session, index CRT was recorded. IHI was noted down 30 minutes before the beginning of intermittent hemodialysis and then 60 minutes, 120 minutes and 180 minutes. Entire data were recorded as a predesigned proforma. The natural distribution of patients into subgroups was done using Chi Square test considering p-value ≤0.05 as significant Results: The total population was 98 men (71.5%) and 39 women (28.5%) Average age was 61.51 ± 15.37 years. 45(17.5%) patients observed abnormal Capillary refill time. 20(14.6%) patients experienced intradialytic hemodynamic instability. Among patients diagnosed with intradialytic hemodynamic instability, 9(45%) had abnormal CRT. Compared to patients with normal CRT, individuals with aberrant CRT had a higher risk of hemodynamic instability (OR = 5.564, p < 0.001). Conclusion: IHI was most at risk when it comes to initiating intermittent hemodialysis, especially in the first hour of the first session. The increase in index capillary refill time was linked to IHI.